Patrimônio cultural imaterial - Tutela jurídica e administrativa - Silva, Andréa Cláudia Sales (2017)
The legal relevance of intangible cultural heritage came with the adoption of a unitary and systemic conception of the Federal Constitution of 1988, which inserted in art. 216, the cultural good in the role of environmental goods. In view of this importance, the present study intends to analyze the protection of intangible cultural heritage, in order to verify its preservation, as well as its respective tutelage, seeking to verify the difficulties for the preservation of the National Intangible Cultural Heritage. With this, the work will discuss the extent to which the Brazilian legislation for the protection of intangible cultural heritage is effective in protecting these assets. For this, an analysis was made of some institutes for the protection of cultural heritage and environmental law. Also will be studied the issues related to the administrative tutelage of the Brazilian cultural heritage, as well as the constitutional instruments of protection to the Brazilian cultural patrimony. Considering the objectives of the research, the method of deductive approach was adopted, using indirect documentation and bibliographic research through books, periodicals, articles, and virtual vehicles related to the theme. Keywords: Preservation. Intangible cultural heritage. Legal protection.